Study of Efficiency and Reaction Rates Dechlorination of Nata De Coco Wastewater Using Sodium Thiosulfate - Sari, Alifiana Permata; Rhamadani, Fadila Arum; Amanah, Nur Layli; Nugroho, Agung (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2022)
Chemical reduction with sodium thiosulfate is commonly used to dechlorinate chlorinated waste. U.S. Environmental Protection Agency recommends sodium thiosulfate (Na2S2O3) as a dechlorinating agent for waste samples containing residual chlorine before being released into the environment or entering the distribution system. However, sodium thiosulfate's efficiency and chlorination kinetics at different concentrations are still unknown due to a lack of information on chlorination kinetics. The study was conducted by determining the number of efficient doses of sodium thiosulfate and observing chlorination kinetics using sodium thiosulfate as a dechlorination agent observed at different stoichiometric ratios (1x, 1.5x, and 2x). Sodium thiosulfate at a stoichiometric dose of 2x can reduce chlorine residue by up to 0.4 ppm. The regression analysis of and constant rate are used in the kinetic analysis of sodium thiosulfate dechlorination processes. The kinetics of the chlorination process employing sodium thiosulfate is first order to the total concentration of chlorine in solution at a stoichiometric dosage of 2x, according to the findings.